The Practice of Radicalism: A Bibliometric Analysis - Taqwa Sihidi, Iradhad; Mutiara Hati, Erva; Romadhan, Ach. Apriyanto (Technium Social Sciences Journal, 2024)
This study aims to conduct a bibliometric analysis of the theme of radicalism. This topic has always been the center of attention because radicalism is one of the world's problems or phenomena faced by many countries. By using the Scopus database from 2016 to 2021, concept mapping and clustering related to the theme of radicalism will be seen. The data was collected through a search on the Scopus database with the keyword radicalism. The data analysis focused on cluster analysis, dominant topics, related themes, and mapping of radicalism study topics based on the number of articles visualized and analyzed using VOSviewer software. This research shows that the study of radicalism has five dominant keywords that often appear, namely Radicalism, Islamism, terrorism, Religion, and Identity. This shows that the five topics are the main focus of attention written by most authors. This research contributes to delivering the development and mapping of the study of radicalism as one of the problems in global democracy. Meanwhile, the limitation is that the articles reviewed are only sourced from Scopus, so they do not have comparative data. Therefore, future studies require using a comparative analysis approach that uses a Web of Science (WoS) database.